Creative thinking in Turkish language education - Batdi, Veli; Doğan, Yunus; Erdem, Tuğba; Yilmaz, Islim Derya; Akdağ, Ismail (Nova Science Publishers, Inc., 2024)
In our rapidly evolving era, technological advancements continuously generate and disseminate new knowledge, necessitating individuals to enhance their creative thinking skills to adapt to this rapid change. Creative thinking, the ability to create original, new, and different products by establishing novel relationships between events, situations, and objects, is vital in the information age. Education plays a pivotal role in developing this skill, with educational environments, teacher approaches, and learning activities significantly influencing its cultivation. The acquisition of creative thinking skills is a shared objective across all disciplines, and the Turkish language course, which focuses on native language education, holds particular importance in this regard due to the strong link between language and thinking. Through an activity-based approach, individuals can acquire skills in listening, speaking, reading, and writing. Creative thinking skills, being fundamental, can be nurtured through activities aimed at enhancing comprehension and expression in Turkish lessons. Activities designed to improve listening and speaking skills can effectively foster creative thinking. Listening, a foundational language skill, is essential for acquiring information and is a prerequisite for creativity. Creative listening activities in classrooms significantly contribute to creative thinking by encouraging the interpretation of what is heard and generating new ideas. Collaborative activities, such as summarizing texts, identifying cause- and-effect relationships, and making predictions, can further develop creative thinking skills. Similarly, reading involves complex mental activities beyond mere pronunciation. Adopting a constructivist education approach, creative reading entails approaching texts with original perspectives and reaching new interpretations. Quality children's literature and activities that stimulate creative thinking should be incorporated to promote creative reading. Textbooks should be organized with activities and visual elements conducive to developing creative thinking. In today's visually driven world, individuals also encounter information through visual channels. Interpreting visual information and creating graphics and tables can activate creative thinking. Speaking, as a skill based on self-expression, can be developed through planned activities such as discussions and problem-solving, fostering communication, critical thinking, and empathy. Drama, acting, and role-playing techniques enhance speaking activities by facilitating interaction and engaging individuals through all senses, thereby promoting gains such as creative thinking and collaboration. Writing, often perceived as tedious, requires organizing thoughts and expressing them in an original language. Employing creative writing activities based on process-based stages, such as creative drama and music, encourages interest and enjoyment in writing, fostering creativity and critical thinking. By integrating these approaches into educational practices, individuals can be encouraged to develop and utilize their creative thinking skills effectively, enabling them to navigate the complexities of our rapidly evolving world. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Comprehension skills; Creative thinking; Turkish language teaching